TRANSITIVITY OF A GENETICALLY AND SOCIALLY DETERMINED LANGUAGE PARADIGM (Scientific journal of the Fergana State University, 2023)
The article highlights the problem of scientific identification of a transitive, genetically and socially determined language paradigm. The idea of the genetic substance of the brain as the generative basis of language is substantiated. The process of formation of sign structures of language at the junction of intentions of the deep sphere with meaningful mental constructs of socio-cultural information is shown